On the Origin and Fate of Reactive Oxygen Species in Plant Cell Compartments - Martina Janků; Lenka Luhová; Marek Petřivalský (MDPI AG, 2019)
Reactive oxygen species (ROS) have been recognized as important signaling compounds of major importance in a number of developmental and physiological processes in plants. The existence of cellular compartments enables efficient redox compartmentalization and ensures proper functioning of ROS-dependent signaling pathways. Similar to other organisms, the production of individual ROS in plant cells is highly localized and regulated by compartment-specific enzyme pathways on transcriptional and post-translational level. ROS metabolism and signaling in specific compartments are greatly affected by their chemical interactions with other reactive radical species, ROS scavengers and antioxidant enzymes. A dysregulation of the redox status, as a consequence of induced ROS generation or decreased capacity of their removal, occurs in plants exposed to diverse stress conditions. During stress condition, strong induction of ROS-generating systems or attenuated ROS scavenging can lead to oxidative or nitrosative stress conditions, associated with potential damaging modifications of cell biomolecules. Here, we present an overview of compartment-specific pathways of ROS production and degradation and mechanisms of ROS homeostasis control within plant cell compartments.